Experiences and perceptions of youth living with HIV in Western Uganda on school attendance: barriers and facilitators - Emmanuel Kimera; Sofie Vindevogel; Mugenyi Justuce Kintu; John Rubaihayo; Jessica De Maeyer; Didier Reynaert; Anne-Mie Engelen; Fred Nuwaha; Johan Bilsen (BMC, 2020)
Abstract Background The globally recognized socio-economic benefits of education have stirred many countries in Sub-Saharan Africa like Uganda to promote universal access to schooling by removing fiscal barricades for those in primary and secondary schools. However, the proportion of Youth Living With HIV/AIDS (YLWHA) missing school, studying with difficulties and dropping out of school in Uganda has been observed to be higher than that of other youth. This study aimed at understanding the barriers and facilitators for YLWHA in Uganda to attend school. Methods We conducted a qualitative inquiry with 35 purposively selected YLWHA aged 12 to 19 years, including 16 females at three accredited Antiretroviral Therapy (ART) treatment centres in Kabarole district in Western Uganda. Individual semi-structured interviews were tape-recorded, transcribed verbatim and subjected to thematic inductive analysis. Results We identified five main themes in which barriers to attend school were reported and four main themes in which facilitators were reported by participants. The main themes for barriers were: 1) management of ART and illnesses, 2) fear, negative thoughts and self-devaluation, 3) lack of meaningful and supportive relationships, 4) reactionary attitudes and behaviours from others at school, 5) financial challenges. The main themes for facilitators were: 1) practical support at school, home and community, 2) counselling, encouragement and spirituality, 3) individual coping strategies, 4) hopes, dreams and opportunities for the future. Conclusion Most of the barriers reported arose from HIV-related stigma and financial challenges whose genesis transcends school boundaries. While YLWHA reported measures to cope, and support from other people, these were non-sustainable and on a limited scale due to disclosure apprehension at school and the indiscretion of those who learnt about their status. To promote supportive school environments for YLWHA, integrated curricular and extracurricular interventions are necessary to increase HIV knowledge, dispel misconceptions about HIV and consequently transform the school community from a stigmatizing one to a supportive one.